1986
DOI: 10.1159/000275859
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Salivary Gland Tumors in Children and Adolescents

Abstract: In the Salivary Gland Register (University of Hamburg), 9883 cases were recorded from 1965 to 1984. Among these cases there were 3,326 neoplasms, of which 3,017 were epithelial in origin. In this latter group, 80 neoplasms arose in children and adolescents. Among these 80 persons, there was a slight predominance of females; 57 tumors (71 %) were localized in the parotid gland, and only 6 (8 %) in the submandibular gland. The incidence of the tumor types was different in children and adolescents as compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(17 citation statements)
references
References 10 publications
2
13
0
2
Order By: Relevance
“…It has been estimated that about 1% to 5% of all salivary gland tumors develop in children and adolescents [1,8], and MEC is the most common malignancy [5,9,39,40]. In the current LSUSD series, 3.5% of the epithelial minor salivary gland neoplasms occurred in patients 19 years of age or younger; this is in close agreement with the series reported by Waldron et al .…”
Section: Discussionsupporting
confidence: 89%
“…It has been estimated that about 1% to 5% of all salivary gland tumors develop in children and adolescents [1,8], and MEC is the most common malignancy [5,9,39,40]. In the current LSUSD series, 3.5% of the epithelial minor salivary gland neoplasms occurred in patients 19 years of age or younger; this is in close agreement with the series reported by Waldron et al .…”
Section: Discussionsupporting
confidence: 89%
“…[17][18][19] Guzzo et al reported that the most common sites are the parotid, submandibular, and sublingual glands. 20 In the present study the male to female ratio was 1:2, similar to previous data from Castro et al 5 and Seifert et al 21 and confirms in the pediatric group the well-known predominance of the salivary gland tumors for the female sex. This was also in line with other studies 22,23 excepting for one study by Shafkat et al 17 which showed that had males have more tendency to develop salivary gland tumors.…”
Section: Discussionsupporting
confidence: 93%
“…A PA is composed of a wide spectrum of epithelial and mesenchymal tissue derived from cells with ductal and myoepithelial features and it is by far the most common salivary gland neoplasm in children [1,32]. Although it is commonly stated that neoplasms of minor salivary glands rarely occur prior to the second decade [33], we found that, when combining the well-documented literature cases with our LSUSD cases, 28.6% of PAs arising from minor salivary glands in children occurred during the first decade of life.…”
Section: Discussionmentioning
confidence: 99%